Aplikasi Beberapa Jenis Pakan Terhadap Pertumbuhan Daphnia magna - Fahmi, Rizkan (Biram Samtani Sains, 2021)
This study aims to analyze the effect of feedingdifferent types of food on the density and growth of Daphnia magna, and determine the best type of feed for the culture of Daphnia magna. This research conducted in Balai Benih Ikan Lukub Badak – Aceh Tengah from Februari to Maret 2020. This study used a completely randomized design with 5 level of treatments 3 replications is : administration of bread yeast at a dose of 0,03 g/l, soy fermentation and doubt fermentation at a dose of 0,06 g/l, and tilapia pond and catfish pond water. The result of this study showed that the highest value was in treatment A with a density of 104, a growth rate of 0, , and a peak population of 104Ind/L.